Sleep Deprevation Effect On The Driving Activity Using Sustained Attention Test - Fandy Valentino; Hardianto Iridiastadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
The rate of train accidents in Indonesia is still high, mainly caused by humans related to fatigue while on duty. One of the factors that influence the level of fatigue is the duration of the previous sleep time which causes the level of alertness at work to decrease. This study aims to determine how significantly a person alertness performance decreases due to sleep deprivation using Sustained Attention Test. The study was conducted with laboratory experiments using a train simulator involving twelve participants aged 21.2 Â± 0.92 years. The independent variable is the duration of sleeping time before driving with a duration of eight hours for normal conditions and a duration of two hours for sleep deprivation. The dependent variable is the parameter on the Sustained Attention Test which is tested before and after driving using the Kruskal-Wallis test. The results showed that there was a increase in the value of the Sustained Attention Test, especially the error and miss parameters which were significant due to sleep deprivation with an average significance of p-value less than 0.05 and increasingly significant with an average of p-value less than 0.01 after driving activity. This shows that sleep deprivation greatly affects the drivers performance while on duty.